Beholding Ourselves: Black Girls as Creators, Subjects, and Witnesses. Issue 3 (1st December 2021) - Stephens, Erin M.; Gilmer, Jamaica
Abstract : The bus was full of excited chatter as it pulled up in front of the Metropolitan Museum of Art (known universally as The Met) on Fifth Avenue on a cold morning in January. Thirteen girls, along with invited loved ones, had traveled for nine-and-a-half hours from Durham, NC, to view their art displayed in the exhibit, "Pens, Lens, and Soul: The Story of The Beautiful Project" (hereafter, "Pens, Lens, and Soul"). First, the girls filed off the bus to take a photograph on the steps of The Met. As their family and friends waited to disembark, they laughed and shivered while posing for numerous photographs and videos on the cold steps. As they stood at the bottom of the steps of the grand prestigious museum, the impressiveness of their accomplishment was just beginning to dawn on many of them. As she walked around the exhibit one of the artists would comment, "I feel surprised because I didn't realize it was this big of a thing and I was here and it's a thing, it's a big thing … we are capable of doing anything."